ECOLOGY AND BREEDING BIOLOGY OF CHESTNUT-TAILED STARLING, STURNUS MALABARICUS (GMELIN 1789) - Jaman, M. F.; Sahreen, N. (Ecoprint: An International Journal of Ecology, 2004)
Studies on the ecology and breeding biology of Chestnut-tailed Starling, Sturnus malabaricus (Gmelin) were carried out from June 1997 to July 1998 in Dhaka and Nilphamari districts. This bird mainly found in parties and small flocks on the upper canopy and leaf of the trees to feed on insects. Breeding season of this bird started from the early February and ended to last July. A total of 30 nests were studied those were found in 5 species of trees and in the ventilation of buildings in five study areas. The peak nesting period was in March. Both sexes took part in nest building, egg incubation, brooding and feeding of nestlings. The mean clutch size was 3 ± 0.63 eggs. Out of 30 eggs belonged to 10 nests, 20 (66.67%) were hatched and the rest 10 (33.33%) were lost and infertile. The mean incubation period was 17 ± 1.3 days. Brood size varied from 1-3 nestlings. Out of 20 nestlings hatched, 10 (50%) were fledged successfully. The breeding success was 33.33% in relation to the number of eggs laid and 50% in relation to the nestlings hatched. The fledging period varied from 19 to 21 days.Key words: Ecology, breeding biology, Chestnut-tailed Starling, Sturnus malabaricus.Ecoprint Vol.11(1) 2004.